Epidermal electronics for respiration monitoring via thermo-sensitive measuring. (June 2020) - Liu, Y.; Zhao, L.; Avila, R.; Yiu, C.; Wong, T.; Chan, Y.; Yao, K.; Li, D.; Zhang, Y.; Li, W.; Xie, Z.; Yu, X.
Abstract: The depth and rate of human respiration reveal important and diverse sets of physiological information for evaluating human health. Here, we introduce an ultrathin, skin-integrated respiration sensor based on the thermal convection effect. The device features a filamentary fractal design of the gold heating electrode, a mini sensor (0.6 mm × 0.3 mm × 0.23 mm) with high thermal sensitivity and an ultrasoft encapsulation package to enhance the overall flexibility and biaxial stretchability of the system. Adjusting the input power of the heating electrode, i.e., increasing the temperature difference between the thermal sensor and environment, can further improve the sensitivity of the respiration sensor. The real-time monitoring respiration sensor can competently distinguish various breathing patterns (sitting, frightening, sleeping, meditating, and gasping) through breath rate/depth of detection subjects. In addition, the respiration sensor can effectively capture, in real time, the respiration of a volunteer while exercising, resting, or sleeping for prolonged periods of time. The combination of advanced mechanics, high sensitivity, and good stability make this respiration sensor a great candidate for potential use in real-time monitoring of human health. Graphical abstract: Image 1 Highlights: Respiration sensors are realized in a thin, flexible, and skin-like format. A combination of thermal convection effect and thermal actuation is used for high-performance respiration sensing. The real-time monitoring respiration sensor can competently distinguish various breathing patterns.